Reaching Rigor for English Learners Through Responsive Interactions of Care - Holmes, Melissa A.; Kavimandan, Shabina K.; Herrera, Socorro G. (IGI Global, 2018)
This chapter explores what happens when teacher-student and student-student interactions reflect a higher level of responsiveness to the human beings involved. It describes biography-driven instruction (BDI), a research-based method of instruction that supports all learners to reach high academic standards, while at the same time ensuring that English learners have the scaffolds and tools needed to engage fully in the curriculum. Teachers who implement BDI develop a holistic understanding of students' sociocultural, linguistic, cognitive, and academic dimensions. They use students' background knowledge as a springboard to new learning. To determine the impact of BDI on the education of English learners in elementary classrooms, this chapter explores the perspectives of 16 teachers (Grades 1-6) who received professional development on BDI and then implemented the method with their own communities of learners. Interview data was collected in Spring 2016, transcribed, and qualitatively analyzed. Findings in the form of themes in participant voice are discussed throughout the chapter.
Citation: Holmes, M., Kavimandan, S., & Herrera, S. (2018). Reaching rigor for English learners through responsive interactions of care. In N. Guler (Ed.), Optimizing elementary education for English language learners (pp. 91-115). Hershey, PA: IGI Global.